Análise sistêmica da cadeia produtiva da polpa de frutas dos territórios Açú-Mossoró e sertão do Apodi (RN) - Oliveira, Isabelle Almeida de (Universidade Federal Rural do Semi-Árido, 2015)
This thesis is part of a set of studies about the rural areas and family farming, considering its aspects in the economic structure, value addition, organizing group and insertion in the marketplace. There's always been missing a lack of public policies for the family farming, however, during these last ten years there have been issued for those lands significant amounts of funds, especially for small production structures. Although those structures constitute one of the most interesting and promising experiences to the countryside, they have worked in disabilities, and its economic dynamism has not happened. In this context, the main matter is how the supply chain of fruit pulp forms has made a set of initiatives that can build a promising new endogenous development format, but it has not been able enough to promote economic dynamism of the lands in Açu-Mossoró and in the countryside of Apodi (RN). By being aware about that, we tried and analyzed in a systematic way the fruit pulp production chain as an environment of innovation and production of new things, considering its role play in the diversification of the local economies, and in taking forward to the lands of Açu-Mossoró and in the countryside of Apodi (RN). As for the methodology to perform the data collecting we've chosen to use the primary data, which was consisted of a questioning in the units of fruit pulp production identified in the studied areas. As a result, the survey revealed that the fruit pulp chain is largely present in the countryside of Apodi than in Acu-Mossoró due to a larger number of production units, more diversified in the family farming, but besides that they have built a better social organization and consolidated group, which led them into their insertion into different markets. However, deficiencies have been identified, such as the lack of trade certification which limits them in the market insertion. This survey found that the lack of infrastructure is related to the lack of credit, technical and technology assistance, leading the farmers to develop their own new strategies and create their own new policies to try and access their join into the markets
Systemic analysis production chain in pulp fruit territories Açu-Mossoró and sertão Apodi (RN)
Keywords: Family farming; Fruit pulp - production chain; Family agribusiness; Public policy; Acu-Mossoro territory - backwoods of Apodi/RN; Agricultura familiar; Polpa de frutas - cadeira produtiva; Agroindústria familiar; Políticas públicas; Território Açu-Mossoró - sertão do Apodi/RN; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE